Human lncRNA RMRP interacts with DEAD-box helicases and modulates mitochondrial function - Higor Sette Pereira; Jason Luddu; Govardhan Reddy Veerareddygari; Shridhar Kiran Sanghvi; Priyanshi B. Patel; Zachary E. Robinson; M. Quadir Siddiqui; Harpreet Singh; Trushar R. Patel (Proceedings of the National Academy of Sciences, 2026)
The human long noncoding RNA (lncRNA) RMRP , initially identified as part of the RNase MRP complex, is linked to various human diseases. However, its structural flexibility and broader cellular roles are not well understood. Here, we offer a comprehensive analysis of RMRP ’s structure in solution, its interactions with human proteins, and its mitochondrial functions. Using small-angle X-ray scattering (SAXS), we show that RMRP adopts different Mg 2+ -dependent shapes, shifting from an extended Y-shaped form to a more compact one as Mg 2+ levels increase. We identified and characterized interactions between RMRP and the DEAD-box RNA helicases DDX5 and DDX3X, with DDX5 binding strongly and exhibiting ATP-dependent helicase activity on RMRP , while DDX3X mainly acts as an expression regulator. Both helicases are crucial for the proper mitochondrial localization of RMRP , working within a complex regulatory network. Functionally, reducing RMRP levels disrupts mitochondrial stability, leading to membrane depolarization and an increase in reactive oxygen species, without affecting cell growth. Mechanistically, RMRP specifically controls nuclear-encoded mitochondrial proteins involved in cristae structure (DNAJC11) and respiratory chain function (NDUFS8). Our results position RMRP as a structurally adaptable lncRNA that collaborates with RNA helicases to preserve mitochondrial health through specific gene regulation. These insights provide perspectives on RMRP ’s biology and the molecular mechanisms underlying RMRP -related disorders, which could inform future therapies for conditions resulting from RMRP dysfunction.